Toxoplasmosis—Awareness and Knowledge of Pregnant Women in Rural Areas of Malakand Region, Pakistan - Wali Khan; Hafeez ur Rahman; Yousef Abdal Jalil Fadladdin; Naseem Rafiq; Robi Naz; Patricio R. De los Rios-Escalante; Shabir Ahmad; Shouaa Abdulaziz Alrobaish; Noorah Saleh Al-Sowayan (Journal of Parasitology Research)
Background. The current study was carried out between October 2017 and October 2018 to explore knowledge, attitudes, practices, and information sources regarding toxoplasmosis among pregnant women in Malakand region, the northwestern part of Pakistan. The current study was carried out between October 2017 and October 2018. Methods. A structured questionnaire was used to interview the women after taking verbal informed consent. Graphpad version 5 was used to indicate the differences. Significant was considered as a P-value of less than 0.05. This study revealed poor knowledge regarding toxoplasmosis. Results. Overall, 31.2% of the respondents showed good knowledge, and 39.2% showed moderate knowledge. On the other hand, 29.5% of the participants showed poor knowledge about toxoplasmosis. The average knowledge score of pregnant women was 79±12.2, which is considered to be within the scale of good knowledge. Number of children within the pregnant multipara women was significantly associated with knowledge about toxoplasmosis. Pregnant women who measured in number of childbirths within a women showed the highest mean score of 42.3±13.3 with 57 (44.8%) displaying a good knowledge level. Pregnant women with more than one child had significantly higher (<0.0001) knowledge scores compared to women with one child or none child. The majority of pregnant women with one child used the social media, followed by mass media as sources of information about toxoplasmosis. Scientific sources of information were used more commonly by pregnant women with none of the child birth. Conclusion. Pregnant women knowledge regarding toxoplasmosis was poor as compared to attitudes and practices. Health workers and newspapers/magazines were the main sources of information.